Language put to the test by time: Carlo ginzburg and its contributions to the history of education - Paziani, Rodrigo Ribeiro; Neto, Humberto Perinelli [UNESP] (FapUNIFESP (SciELO), 2018)
The historiographical production of Carlo Ginzburg seems to be increasingly consolidated in Brazil, to the point of being the target of numerous analyzes, interpretations and criticisms. However, this historian is still little known by the academic public, with prominent intellectuals who focus on the history and history of education. Starting from this context, the central proposal of this article will be to promote reflections on the “indicial paradigm” proposed by Ginzburg. For that, we present the formative course, the theoretical-methodological works and the analytical perspectives of this historian, as well as possible relations that can be established with the Language domains, specifically Discourse Analysis, in the case of the current represented by Michel Pêcheux.
A linguagem posta Ç prova pelo tempo: Carlo ginzburg e suas contribuiÇÕes para a histÓria da educaÇÃo
Keywords: Carlo Ginzburg; Discourse analysis; History of education; Language; Theory of history